Ruptured Endometrioma with Hemoperitoneum Requiring Emergency Laparotomy: A Case Report - Rai, Sangam; Dangal, Ganesh; Karki, Aruna; Pradhan, Peru; Shrestha, Ranjana; Bhattachan, Kabin; Maharajan, Sunita; Bhandari, Srijana; Basnyat, Amog (Journal of Nepal Health Research Council, 2024)
Endometrioma is the localization of endometriosis in ovary which often develops as cyst. The condition can be complicated with infection, torsion and rupture leading to significant hemoperitoneum and ascites. We present here a 28-year female P2 L1 presented with the features of acute abdomen and severe anemia referred from other hospital where pain management was done. She had raised Ca-125 level, negative Urine Beta HCG and USG findings of left endometrioma with degenerating subserosal fibroid. The improvement of her general condition with analgesics was misleading however a static hematocrit level despite blood transfusion raised suspicion of ongoing pathology leading to blood loss and diagnostic paracentesis confirmed the hemoperitoneum while awaiting of CT report. She underwent Emergency Laparotomy which revealed hemoperitoneum of 2000ml and right ruptured ovarian endometrioma measuring and left ovarian cyst measuring 6x6 cm was noted. The postoperative period was uneventful. Keywords: Acute abdomen; case report; endometriosis; hemoperitoneum; ruptured endometrioma.